Pemanfaatan Potensi Bambu sebagai Bahan Baku Pembuatan Dustbin di Desa Sedayu Kecamatan Gemuh Kabupaten Kendal - Aulia Ainis Lisa; Novi Syafa’atun; Heru Susanto; Muhammad Rafly Pramudya (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Sedayu Village, located in Gemuh District, Kendal Regency, has abundant natural resource potential. The majority of people develop various kinds of plants and trees to be used as business fields, one of which is bamboo. Bamboo as an abundant and easily renewable natural resource has great potential to be developed as a raw material for making environmentally friendly products. In addition to looking at the characteristics of bamboo both physically and mechanically, this bamboo has good quality to be applied as a raw material for crafts such as dustbin. This research aims to explore the potential of bamboo as a raw material for making dustbin in Sedayu Village with a focus on the advantages, manufacturing process and implementation strategy. This study uses a qualitative approach with a case study design that focuses on getting an overview of local conditions. Meanwhile, data collection is carried out by participatory observation, interviews and documentation. The results of the study show that bamboo has strength and rigidity that exceeds other materials, making it a good structural choice for construction. This research discusses the use of bamboo as a raw material for making dustbin in Sedayu Village. The advantage of bamboo dustbin is its strength. In addition to being able to last a long time outdoors, bamboo also has aesthetic elements, namely its characteristics that are very suitable for rural environments and contain local traditional values that have been passed down from generation to generation.